ASPEK PERKAWINAN DALAM NOVEL BENANG-BENANG SAMBEN KARYA DJELANTIK SANTHA ANALISIS SOSIOLOGI SASTRA - Dwijayanti, Ni Kadek (Humanis; Volume 9. No. 3. Desember 2014)
This study, entitled "Aspek Perkawinan dalam Novel Benang-Benang Samben Karya Djelantik Santha Analisis Sosiologi Sastra". This study uses the theory Sociology of Literature which refers to the structure and system of customary marriage in Bali. This study aims to describe the structure of the build Novel Benang-Benang Samben and examine and analyze various forms of marriage are reflected in the Novel Benang- Benang Samben. The method used in the stage of providing data using methods refer to the technical note. In addition, using interviews with recording techniques and record the important things gained from the interviews. Furthermore, in the stage of data analysis using descriptive qualitative and quantitative methods supported by. In this stage also supported by descriptive analytic techniques. At the presentation stage of data analysis, the method used is formal and informal methods. The techniques used in this phase is a technique in the analysis flow scheme. The results of this study indicate that; (1) analyzes the structure of the build Novel Benang-Benang Samben six that incident, plot, character and characterization, setting, theme, and the mandate, (2) forms of marriage contained in the Novel Benang- Benang Samben by Balinese customary law recognizes two forms namely marriage, ordinary marriage and marriage nyentana, and there are also other forms of marriage contained in the Novel Benang-Benang Samben marriage on pada gelahang. While the method or system of customary law marriage by Bali today is known that there are two ways, namely by way of marriage memadik and marriage by means ngerorod (run together). Both methods are chosen depending on the engagement process (magelanan), (3) The prohibition in marriage is a marriage with kin (gamia gamana), as well as the issues contained in the story of polygamy Novel Benang-Benang Samben.Novel, Marriage, Structure.
Keywords: Novel, Marriage, Structure.